Steelhead trout Oncorhynchus mykiss metabolic rate is affected by dietary Aloe vera inclusion but not by mounting an immune response against formalin-killed Aeromonas salmonicida - Zanuzzo, F. S. [UNESP]; Urbinati, E. C. [UNESP]; Nash, G. W.; Gamperl, A. K. (Wiley-Blackwell, 2015)
The oxygen consumption (MO2) of two groups of 10 degrees C acclimated steelhead trout Oncorhynchus mykiss was measured for 72 h after they were given a 100 mu l kg(-1) intraperitoneal injection of formalin-killed Aeromonas salmonicida (ASAL) or phosphate-buffered saline (PBS). In addition, plasma cortisol levels were measured in fish from both groups prior to, and 1 and 3 h after, they were given a 30 s net stress. The first group was fed an unaltered commercial diet for 4 weeks, whereas the second group was fed the same diet but with 05% (5 g kg(-1)) Aloe vera powder added; A. vera has potential as an immunostimulant for use in aquaculture, but its effects on basal and acute phase response (APR)-related metabolic expenditures and stress physiology, are unknown. Injection of ASAL v. PBS had no measurable effect on the MO2 of O. mykiss indicating that the APR in this species is not associated with any net increase in energy expenditure. In contrast, incorporating 05% A. vera powder into the feed decreased routine metabolic rate by c. 8% in both injection groups and standard metabolic rate in the ASAL-injected group (by c. 4 mg O-2 kg(-1) h(-1); 5%). Aloe vera fed fish had resting cortisol levels that were approximately half of those in fish on the commercial diet (c. 25 v. 50 ng ml(-1)), but neither this difference nor those post-stress reached statistical significance (P > 0.05).
Keywords: acute phase response; bacterial antigen; cortisol; immune function; immunostimulant; metabolic costs